Information technologies in biomedicine : Third international conference, ITIB 2012, Gliwice, Poland, June 11-13, 2012. Proceedings - Kawa, Jacek; Piętka, Ewa (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 4th International Conference on Information Technologies in Biomedicine, ITIB 2012, held in Goglin, Poland, in June 2012. The 60 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on image analysis; signal processing; biocybernetics; biomaterials; bioinformatics and biotechnology; biomechanics and rehabilitation; assisted living systems.